2016
DOI: 10.3389/fnagi.2016.00203
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal Brain Volume Is Associated with Faster Facial Emotion Identification in Older Adults: Preliminary Results

Abstract: Quick correct identification of facial emotions is highly relevant for successful social interactions. Research suggests that older, compared to young, adults experience increased difficulty with face and emotion processing skills. While functional neuroimaging studies suggest age differences in neural processing of faces and emotions, evidence about age-associated structural brain changes and their involvement in face and emotion processing is scarce. Using structural magnetic resonance imaging (MRI), this st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 69 publications
2
14
0
Order By: Relevance
“…Similar to Aas et al (2012) , we did not find a significant association between childhood trauma and hippocampal volumes. However, we did observe a significant positive association between the ERT total score and the total, left and right volumes of the hippocampus, which is consistent with previous studies ( Fujiwara et al , 2007 ; Szymkowicz et al , 2016 ). In terms of our mediation hypothesis, the hippocampus was not observed to mediate the effects of childhood trauma on emotion recognition in either group.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Similar to Aas et al (2012) , we did not find a significant association between childhood trauma and hippocampal volumes. However, we did observe a significant positive association between the ERT total score and the total, left and right volumes of the hippocampus, which is consistent with previous studies ( Fujiwara et al , 2007 ; Szymkowicz et al , 2016 ). In terms of our mediation hypothesis, the hippocampus was not observed to mediate the effects of childhood trauma on emotion recognition in either group.…”
Section: Discussionsupporting
confidence: 93%
“…We also observed a significant positive association between emotion recognition and the total, left and right volumes of the ACC. Consistent with these findings, several studies have suggested that better ability to recognise emotions is associated with larger ACC volumes in both clinical and non-clinical populations ( Fujiwara et al , 2007 ; Szymkowicz et al , 2016 ).…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…As we grew older, cognitive intelligence and EI exhibited distinct trajectories of development (Williams et al, 2006 , 2008 ; Giedd, 2008 ). Although not fully understood, different age groups showed differences in these behaviors that were both accompanied by the human brain morphological and functional changes (Schnack et al, 2015 ; Szymkowicz et al, 2016 ; Xia et al, 2019 ). In more detail, cognitive intelligence, such as memory and processing speed, showed a rapid increase during childhood and adolescence, which peaked around 20s to 30s and then gradually declined throughout the later part of the life span, particularly after 50 years of age (Salthouse, 2009 , 2012 , 2017 ; Singh-Manoux et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, there has been little previous research on FER RT. Some studies have shown that hippocampal brain volume in older adults is positively correlated with the speed of correct FER (Szymkowicz et al 2016). Another study including patients with FSZ showed that RT for a high degree of disgust FER task was longer than HCs and increased activation of the left and right middle temporal gyrus and right caudate in response to the high degree of disgust stimulus (Yang et al 2018).…”
Section: Discussionmentioning
confidence: 99%